Comparative genomics and DNA methylation analysis of Pseudomonas aeruginosa clinical isolate PA3 by single-molecule real-time sequencing reveals new targets for antimicrobials - Li, Zijiao; Zhou, Xiang; Liao, Danxi; Liu, Ruolan; Zhao, Xia; Wang, Jing; Zhong, Qiu; Zeng, Zhuo; Peng, Yizhi; Tan, Yinling; Yang, Zichen (Frontiers in Cellular and Infection Microbiology, 2023)
Pseudomonas aeruginosa (P.aeruginosa) is an important opportunistic pathogen with broad environmental adaptability and complex drug resistance. Single-molecule real-time (SMRT) sequencing technique has longer read-length sequences, more accuracy, and the ability to identify epigenetic DNA alterations. This study applied SMRT technology to sequence a clinical strain P. aeruginosa PA3 to obtain its genome sequence and methylation modification information. Genomic, comparative, pan-genomic, and epigenetic analyses of PA3 were conducted. General genome annotations of PA3 were discovered, as well as information about virulence factors, regulatory proteins (RPs), secreted proteins, type II toxin-antitoxin (TA) pairs, and genomic islands. A genomewide comparison revealed that PA3 was comparable to other P. aeruginosa strains in terms of identity, but varied in areas of horizontal gene transfer (HGT). Phylogenetic analysis showed that PA3 was closely related to P. aeruginosa 60503 and P. aeruginosa 8380. P. aeruginosa's pangenome consists of a core genome of roughly 4,300 genes and an accessory genome of at least 5,500 genes. The results of the epigenetic analysis identified one main methylation sites, N6methyladenosine (m6A) and 1 motif (CATNNNNNNNTCCT/AGGANNNNNNNATG). Though their associated methyltransferases have not yet been found. 16 meaningful methylated sites were picked. Among these, purH, phaZ, and lexA are of great significance playing an important role in the drug resistance and biological environment adaptability of PA3, and the targeting of these genes may benefit further antibacterial studies. This study provided a detailed visualization and DNA methylation information of the PA3 genome and set a foundation for subsequent research into the molecular mechanism of DNA methyltransferase-controlled P. aeruginosa pathogenicity.